2015
DOI: 10.1101/cshperspect.a017590
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Conflict Arising from Extrapair Matings in Birds

Abstract: The discovery that extrapair copulation (EPC) and extrapair paternity (EPP) are common in birds led to a paradigm shift in our understanding of the evolution of mating systems. The prevalence of extrapair matings in pair-bonded species sets the stage for sexual conflict, and a recent focus has been to consider how this conflict can shape variation in extrapair mating rates. Here, we invert the causal arrow and consider the consequences of extrapair matings for sexual conflict. Extrapair matings shift sexual co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Females may gain genetic or direct benefits for offspring through multiple, extrapair mating (Foerster et al 2003;Suter et al 2007;Townsend et al 2010). However, the hypothesis that females elevate fitness through multiple mating is not consistently supported, and substantial costs are also possible, for instance, injury, disease transmission, and loss of paternal support (Westneat and Rambo 2000;Westneat and Stewart 2003;Albrecht et al 2006;Akçay and Roughgarden 2007;Chaine et al 2015). Rather than deriving benefits, extrapair mating by females may instead occur due to male coercion (Westneat and Stewart 2003), or arise through nonadaptive genetic correlation with males (Halliday and Arnold 1987;Forstmeier et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Females may gain genetic or direct benefits for offspring through multiple, extrapair mating (Foerster et al 2003;Suter et al 2007;Townsend et al 2010). However, the hypothesis that females elevate fitness through multiple mating is not consistently supported, and substantial costs are also possible, for instance, injury, disease transmission, and loss of paternal support (Westneat and Rambo 2000;Westneat and Stewart 2003;Albrecht et al 2006;Akçay and Roughgarden 2007;Chaine et al 2015). Rather than deriving benefits, extrapair mating by females may instead occur due to male coercion (Westneat and Stewart 2003), or arise through nonadaptive genetic correlation with males (Halliday and Arnold 1987;Forstmeier et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…First, females may seek out copulations with extra‐pair males if this increases their reproductive success even though these EPCs reduce the reproductive success of their social mate (Westneat and Stewart , Székely et al ). Interactions between the female, her social mate and other members of the population can lead to complex dynamics, since the social mate may retaliate and subsequently reduce his care (Chaine et al ). Second, EPP can lead to brood desertion whereby one, or both, parents abandon their young and seek out new mates to increase their reproductive success (Székely ).…”
mentioning
confidence: 99%
“…Covert EPCs unbeknownst to their social partner present to be a reliable counterstrategy that allows females to benefit from mating multiply but also offset any potential loss of male care. Sexual conflict now becomes a multiplayer game not only involving a male–female pair but also extra‐pair partner/s …”
Section: A Battle Ensues: An Introduction To Male Manipulation and Fementioning
confidence: 99%
“…For example, serial monogamy will create conflict over parental care, while female multiple mating (polyandry), including pair-bonds with extra-pair copulations (EPCs) and multipartner systems, will lead to conflict over parental care and fertilization. 42 A number of theories have been developed to account for the evolution of polyandry, [43][44][45] and empirical studies have confirmed that females can gain fitness benefits by copulating with more than one male to create a situation where rival ejaculates compete for fertilizations. [46][47][48][49][50][51][52][53][54] Selection via sperm competition is expected to favor traits that enhance competitive paternity success and elevate male fitness.…”
Section: A Battle Ensues: An Introduction To Male Manipulation and Fementioning
confidence: 99%
See 1 more Smart Citation